Effect of Different Inoculum Levels of Meloidogyne incognita on the Germination and Early Development of Vegetable Crops - and N. Romabati Devi1, Kh. Solitary Devi1*, L. Joymati Devi2 (Journal of Experimental Sciences, 2011)
Cow pea, broad bean and french bean are important vegetable crops widely grown in North East part of India including Manipur. Root- knot nematode (Meloidgyne incognita) causes heavy losses in these crops. Experiments were carried out to study the effect of M. incognita on germination by inculating in different inoculum level i.e., 0 (control), 10, 100, 1000 and 10,000 second stage juveniles per 200 gm. of soil. With the increase of inoculum levels of M. incognita, there was a progressive decrease in the rate of germination and in growth parameters of the crops. Significant reduction in the length of short, root and weight of whole germinated seed were found in 10,000 inoculum level. The number of larvae penetrated into root and soil were significantly increased as the inoculum level increased.